Cockle Shell as An Additive in Cement Sand Brick Mixture - Abdul Aziz, Mohamed Firdaus; Abdul Jabbar, Muhammad Azri; Azman, Fatin Basirah; Abdul Malek, Khairul Zaman (Multidisciplinary Applied Research and Innovation, 2022)
This article explores the use of the cockle shell (CS) as an additive in cement-based material since the CS is high in calcium oxide (CaO), which can affect the behavior and properties of mortar. The waste cockle shells (WCS) dumped from restaurant retrieved from seafood menus might cause environmental pollution and also discomfort to the surrounding communities. The main goal of this project is to produce cement sand brick (CSB) by adding 10g, 20g and 30g of CS as an additive in mix design according to certain specifications. Density test, water absorption rate test and compressive strength test were conducted on the 7th and 14th day. The results were compared based on mix design and day of testing. It is interesting to find out that the existance of chemical composition in CS affect density, water absorption rate and compressive strength. Oyster shell is highly recommended for future study as an additive in CSB mixture.